Factors Associated With Airline Cabin Crews' Influenza Vaccination Intention in the Workplace-based Setting. (May 2023) - Kim, Layoung; Kim, Gwang Suk; Lee, Kyung Hee; Kim, Jungha
Background: Yearly influenza vaccination is the best way to prevent influenza. Workplace vaccination program for airline cabin crews is an important countermeasure in the management of infectious diseases. Understanding the influenza vaccination behavior of cabin crews is essential to establishing strategies to promote vaccine uptake. This study aimed to examine factors associated with airline cabin crews' influenza vaccination intention in a workplace-based setting. We applied the theory of planned behavior (TPB) to explain the vaccination behavior of employees. Methods: A cross-sectional study was performed in April 2021. Participants self-reported the structured questionnaires that consisted of TPB variables, and reasons for influenza vaccination/nonvaccination in 2020. A total of 253 crew members participated, and 242 were included in the analysis. Findings: The influenza vaccination rate was 70.7% in 2020, and vaccination intention was 5.92 of 7 points in 2021. Multiple linear regression showed that influenza vaccination intention was associated with subjective norms (β = .394, p < .001), positive attitude (β = .145, p = .007), perceived behavioral control (β = .170, p = .004), actual behavioral control (β = .145, p = .010), and the previous year's vaccination (β = .163, p < .001). The model accounted for 57% of the variance in influenza vaccination intention ( F = 40.959, p < .001). Conclusions/Application to Practice: Our findings indicate that TPB is useful in explaining employees' influenza vaccination intention and influencing factors. Focusing on positive messages that emphasize the social effects of vaccination and providing free vaccination on specific dates are potential strategies to increase intention. It can be applied to help design on-site workplace vaccination programs for essential frontline workers.